Investigation of the safety factor of a pile with increases seismicity areas - Родченко, О.В.; Ляшенко, Л.А. (Proceedings of National Aviation University (archive), 2009)
Research the coefficient of supply of pile is conducted subject to the condition increase of seismic of site from six to seven marks. As a result of calculation in the ПК Мономах of three buildings with different structural charts at the seismic loadings six and seven marks were shown out coefficient of supply of pile and character of his change is set depending on the structural features of building.